2017
DOI: 10.1016/j.gene.2017.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Genetic regulation of adipose tissue transcript expression is involved in modulating serum triglyceride and HDL-cholesterol

Abstract: Dyslipidemia is a major contributor to the increased cardiovascular disease and mortality associated with obesity and type 2 diabetes. We hypothesized that variation in expression of adipose tissue transcripts is associated with serum lipid concentrations in African Americans (AAs), and common genetic variants regulate expression levels of these transcripts. Fasting serum lipid levels, genome-wide transcript expression profiles of subcutaneous adipose tissue, and genome-wide SNP genotypes were analyzed in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
(50 reference statements)
1
7
0
1
Order By: Relevance
“…Additionally, in immunoinflammatory pathways, genes were activated among individuals with higher serum TG levels. 29 Furthermore, in this study, the genotypes GA and AA of rs2710642 and genotypes TC and CC of rs10496099 were correlated with low serum TG levels in the Maonan population and some haplotypes of EHBP1 rs2710642 and rs10496099 SNPs modulated serum lipid levels. As a dominant haplotype in both the Han and Maonan populations, rs2710642A− rs10496099C was a potential protective factor for slightly increasing serum ApoA1 or HDL-C levels and decreasing TC and TG levels, but rs2710642G−rs10496099C was a damaging factor with the opposite trendsdecreasing HDL-C and increasing TC, TG, or LDL-C serum levels.…”
Section: ■ Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Additionally, in immunoinflammatory pathways, genes were activated among individuals with higher serum TG levels. 29 Furthermore, in this study, the genotypes GA and AA of rs2710642 and genotypes TC and CC of rs10496099 were correlated with low serum TG levels in the Maonan population and some haplotypes of EHBP1 rs2710642 and rs10496099 SNPs modulated serum lipid levels. As a dominant haplotype in both the Han and Maonan populations, rs2710642A− rs10496099C was a potential protective factor for slightly increasing serum ApoA1 or HDL-C levels and decreasing TC and TG levels, but rs2710642G−rs10496099C was a damaging factor with the opposite trendsdecreasing HDL-C and increasing TC, TG, or LDL-C serum levels.…”
Section: ■ Discussionsupporting
confidence: 48%
“…Blood lipids also circulate to damaged intima and are retained in the intima, mainly triggering atherosclerosis, CVD, and ischemic stroke. Additionally, in immunoinflammatory pathways, genes were activated among individuals with higher serum TG levels . Furthermore, in this study, the genotypes GA and AA of rs2710642 and genotypes TC and CC of rs10496099 were correlated with low serum TG levels in the Maonan population and some haplotypes of EHBP1 rs2710642 and rs10496099 SNPs modulated serum lipid levels.…”
Section: Discussionmentioning
confidence: 49%
“…Published evidence implicated these 18 genes directly through population studies (GBP6, GSTO1, HHIPL1, INTS10, RGS16 and RNU6-679P), indirectly through association with other metabolic conditions (CCDC69, DNAH2, GALNT17, HERC5, KIF5C, MARCH2 and PRDM14) or through association with complications of T2D (CASC15, CCDC107, MIR147A, PFKFB3 and RNF166). Detailed annotation of the published literature in this regard is provided in Supplementary Table S3 ) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. From the remaining genes identified to be significantly associated with T2D in this study, there were two open reading frames, three long intergenic non-coding elements and a pseudogene.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the present study focused on identifying transcriptional mechanisms associated with composite gluco-metabolic phenotypes. Our previous studies showed that a subset of gluco-metabolic trait GWAS-identified SNPs are cis-eSNPs ( 11 ; 31 ). Herein, we demonstrate that expression of a subset of CP-associated transcripts is determined by cis-eSNPs, and CP-associated transcripts are among the genes predicted by bioinformatics analysis of GWAS-implicated BMI loci.…”
Section: Discussionmentioning
confidence: 99%